Compilation and validation of a parenting package based on the healthy human theory for mothers with children with externalizing disorders - Khansari, Zahra; Torkan, Hajar; Bahramipour, Mansoureh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted considering the breadth and comprehensiveness of the healthy human theory and its culture-based nature, with the aim of compiling and validating a parenting package based on the healthy human theory, especially for mothers with children with externalizing disorders. Method: The qualitative research method was an exploratory type (thematic analysis) inductive problem and need based on the process and rules of content analysis by Strauss and Corbin, and the content analysis method was used to compile the parenting package based on the healthy human theory. The research area includes 34 scientific texts that were selected by purposeful sampling and based on the relationship between the content and healthy human education strategies; Also, the professors and faculty of the Department of Psychology and Counseling of Isfahan Islamic Azad University, 6 of them were selected as a sample in order to evaluate the parenting package based on healthy people. Results: The results of the method of Strauss and Corbin (1998) showed that 9 selected codes (being present, kindness to creatures, satisfaction with life and enjoyment, happiness, metacognition, forgiveness and forgiveness, forgetting, peace and meaning, hope) and the parenting package based on the healthy human theory was adjusted based on these dimensions according to the frequency of the semantic units of the selected codes, and its reliability and validity were confirmed based on the approval of experts and the agreement coefficient of the evaluators, which was 0.99. Conclusion: Therefore, the compiled package, which is based on the culture of Iranian families, can be used to educate parents, especially mothers of children with behavioral problems, in order to improve their quality of life.